Adult-to-Adult Living Donor Liver Transplantation - Shimul A Shah; Gary A Levy; Lesley D Adcock; Gary Gallagher; David R Grant (Canadian Journal of Gastroenterology)
The present review outlines the principles of living donor liver transplantation, donor workup, procedure and outcomes. Living donation offers a solution to the growing gap between the need for liver transplants and the limited availability of deceased donor organs. With a multidisciplinary team focused on donor safety and experienced surgeons capable of performing complex resection/reconstruction procedures, donor morbidity is low and recipient outcomes are comparable with results of deceased donor transplantation.